COMMUNITY CULTURE-BASED SOCIAL CAPITAL EMPOWERMENT - Musa Pelu (Universitas Sebelas Maret, 2017)
This research aimed to describe the social capital empowerment based on community culture in implementing Noble Character Education Curriculum in SMP Muhammadiyah 5 Surakarta. This study was descriptive qualitative research with naturalistic approach. The research was taken place in SMP Muhammadiyah 5 Surakarta. Data collection was conducted through in-depth interview, observation and document analysis. The research instrument was the author himself as data collector. Data validation was carried out using triangulation, recheck, and peer debriefing techniques. Data analysis was conducted using an interactive technique of analysis encompassing data collection, data reduction, data display, and verification/conclusion drawing. From the result of research, the following conclusions could be drawn. (1) The synergic cooperation network based on mutual trust and shared value/norm was the social capital that had been empowered in the attempt of supporting the implementation of noble character education curriculum policy in SMP Muhammadiyah 5 Surakarta. (2) Social Capital supports the creation of noble character- and religion-based school culture in SMP Muhammadiyah 5 Surakarta and community culture. This condition was a main cultural capital utilized and managed in implementing the Noble Character-Education Curriculum.